Antimicrobial activities of Parkinsoniaaculeata and Prosopiskoelziana extracts against pathogenic fungi and bacteria (Staphylococcus aureus, S. epidermidis,S. pyogenes,Pseudomonas Aeruginosa, Escherichia Coli, Aspergillus niger, A. flavus, A. fumigatus,F. solani,Microsporum gypseum, M. mcanis, Trichophyton verrucosum,T. rubrum and Candida albicans) - Seyed reza Hosseini Doust; Fatemeh Mirzaee; Narges Dakhili; Mehdi Razzaghi-Abyaneh (Journal of Pharmaceutical and Health Sciences, 2018)
Parkinsonia aculeata and Prosopis koelziana are two spinous ornamental plant from Leguminosae family. Besides their traditional uses, many pharmacological activities have been reported from family members, although little studies have been done about their antimicrobial properties. Excessive drug resistance and ineffectiveness of some antimicrobial drugs have led to exploitation of natural sources especially plant materials for treatment of infection diseases. Present study was conducted to investigate the antimicrobial properties of methanol extract and different fractions of Parkinsonia aculeata and Prosopis koelziana growing in south of Iran against P. aeruginosa, S. aureus, S. epidermidis, Aspergillus niger, A. flavus, A. fumigatus, M. gypseum and C. albicans. Methanol extract and three fractions of each Parkinsonia aculeata and Prosopis koelziana including ethyl acetate, chloroform and aqueous fractions had been assayed separately against microorganisms. The antimicrobial activities of the extract and fractions were measured by standard agar diffusion Methods (disc-diffusion and well-diffusion methods). The antimicrobial activity was evaluated by measuring the inhibition zones against the test organisms in each method. Methanol extract and chloroform fraction (at 40 mg/ml concentration) demonstrated stronger (20 and 15 mm inhibitory zones) and broader spectrum of antimicrobial activity as compared to other fractions of Parkinsonia aculeate but for Prosopis koelziana, just ethyl acetate fraction was effective (30 and 12 mm inhibitory zones in disk and well-diffusion methods respectively). In disc-diffusion method the highest bacterial and fungal inhibitory zones were related to Pseudomonas aeruginosa and Aspergillus niger by inhibition zones of 20 ± 0.3 and 13 ± 0.1 mm respectively. In well-diffusion assay, the best results were attributed to Aspergillus niger and Staphylococcus aureus with the inhibitory zone of 30 ± 0.2 and 16 ± 0.1 mm. It is concluded that Pseudomonas aeruginosa and Staphyloccus species were more susceptible to the Parkinsonia aculeata extracts and Prosopis koelziana gave best response against Candida albicans and Aspergillus species. These results support the notion that the two plant extracts and fractions may have a role as pharmaceuticals for antimicrobial treatments. It need more extensively studies to explore its potential role in the treatment of infectious diseases.